PKM EDUKASI KEBIJAKAN PENANGGULANGAN STUNTING DI DESA BANJARSARI KECAMATAN GAJAH KABUPATEN DEMAK - Kuswardani Kuswardani; Novita Alfiana; Suci Amanati; Boki Jaleha (JPMUJ, 2026)
Stunting can be seen physically with a child's height being shorter than children of the same age. At this time, nutritional problems still occur and are a national problem. Stunting does not occur suddenly, but can occur over a very long period of time starting from children in the womb to toddlers not getting sufficient nutritional intake. Based on the results of interviews with several community leaders, it was stated that there are still residents of Banjarsari Village, Gajah District, Demak Regency who have insufficient knowledge about the importance of nutritious food to prevent stunting in children. Community service is carried out with the aim of providing an understanding of education about stunting prevention regulation and how to overcome stunting in Banjarsari Village, Gajah District, Demak Regency. After the community service activities, a post-test was carried out and the results obtained were 20 participants who 100% understood stunting prevention regulation and how to deal with stunting in children.